Removal of phthalates in aqueos samples using non-ionic silicone surfactant mediated cloud point extraction via spectrophotometry [Penyingkiran ftalat dalam sampel akues menggunakan teknik pengekstrakan titik awan surfaktan silikon tidak berionik dengan spektrofotometri] - Ooi, Pei Wan; Ramachandran, Muggundha Raoov; Yahaya, Noorfatimah; Nik Mohamed Kamal, Nik Nur Syazni; Gopal, Kasturi; Husin, Nor Aniisah; Zain, Nur Nadhirah Mohamad (Malaysian Analytical Sciences Society, 2019)
Removal of phthalates in environmental compartments become crucial in recent years due to the growing global concern about the health effects of phthalates. In this study, a greener method based on cloud point extraction procedure was developed for the removal of selected phthalates in environmental samples using non-ionic silicone surfactant (DC193C). The parameters affecting the extraction efficiency, such as the surfactant concentration, salt types, salt concentration, temperature and incubation time were evaluated and optimized. Good linearity with correlation coefficients (R2) in the range of 0.9963 – 0.9988 for all calibration curves was obtained. The proposed method was applied in removing the diethhylhexyl phthalate and dibutyl phthalate in river water samples under optimized conditions with satisfactory recoveries in the range of 82 – 98%. © 2019, Malaysian Society of Analytical Sciences. All rights reserved.